2014
DOI: 10.1136/bmjopen-2014-005273
|View full text |Cite
|
Sign up to set email alerts
|

START (STrAtegies for RelaTives) coping strategy for family carers of adults with dementia: qualitative study of participants’ views about the intervention

Abstract: ObjectivesTo analyse the experience of individual family carers of people with dementia who received a manual-based coping strategy programme (STrAtegies for RelaTives, START), demonstrated in a randomised-controlled trial to reduce affective symptoms.DesignA qualitative study using self-completed questionnaires exploring the experience of the START intervention. Two researchers transcribed, coded and analysed completed questionnaires thematically.SettingThree mental health and one neurology dementia clinic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…This evaluation suggests that training for carers, regular reviews and the "Top Tips" information sheets work well in terms of awareness- In addition to improving carer knowledge and skills, it is important to identify ways to address staff and family stress. In the general population, the StaRT (Strategies for RelaTives) support and education programme has been found to be clinically and cost-effective for family carers Livingston et al, 2013) and positively received by carers (Middleton & Mason, 2017;Sommerlad, Manela, Cooper, Rapaport, & Livingston, 2014). This programme is being piloted locally with family carers and a staff team to see how appropriate it is for carers of people with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation suggests that training for carers, regular reviews and the "Top Tips" information sheets work well in terms of awareness- In addition to improving carer knowledge and skills, it is important to identify ways to address staff and family stress. In the general population, the StaRT (Strategies for RelaTives) support and education programme has been found to be clinically and cost-effective for family carers Livingston et al, 2013) and positively received by carers (Middleton & Mason, 2017;Sommerlad, Manela, Cooper, Rapaport, & Livingston, 2014). This programme is being piloted locally with family carers and a staff team to see how appropriate it is for carers of people with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group showed positive effects on carer mood and anxiety levels for 2 years. An accompanying qualitative investigation (Sommerlad et al, 2014) highlighted different components of the intervention that carers identified as important.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%
“…Previous research has suggested that carers of someone with dementia welcome approaches to support that focus on their role in managing the condition (Sommerlad, Manela, Cooper, Rapaport, & Livingston, ). ANs are available to help people in this respect.…”
Section: Introductionmentioning
confidence: 99%